The Effect of Experimental Learning Methods on Students' Cognitive Abilities in Science Learning - Putri, Nindy Rizka Setyaris; Meilana, Septi Fitri (Jurnal Penelitian Pendidikan IPA, 2023)
Learning is a process of teaching and learning activities created by teachers to grow and develop cognitive, affective and psychomotor abilities. At present, there are still teachers who use rote learning methods so that students rarely get the opportunity to voice their opinions, find solutions to problems and participate actively in learning. This study aims to find out and show how experimental learning methods affect students' cognitive abilities in science learning in class IV SDN Ciracas 15 Pagi, East Jakarta. This research is a quantitative descriptive study using a quasy experimental design. A total of 53 students from one of Ciracas Elementary Schools in East Jakarta, both from class IV-A and IV-C were selected as samples using purposive sampling technique. To measure students' cognitive abilities, in this study data collection was carried out using the test method with cognitive ability test instruments in the form of multiple choice questions. Data analysis was performed using the t test. Based on the results of the data analysis, the results of the study show that the experimental class in science learning has significantly higher cognitive abilities, namely xÌ„ = 81.718 compared to students in the control class, namely xÌ„ = 73,857.